Indoor thermal environment assessment of a historic building for a thermal and energy retrofit scenario using a CFD model - Yujin Kang; Hyeonseong Yuk; Ho Hyeon Jo; Sumin Kim (Case Studies in Thermal Engineering)
Research on retrofit scenarios for the energy efficiency of historical buildings is growing. Despite their potential to improve the energy consumption of a building, retrofit scenarios for indoor thermal environments and the thermal comfort of historical buildings has not been sufficiently studied. Therefore, in this study, indoor airflow, heat distribution, and thermal comfort levels of indoor residents were predicted using computational fluid dynamics (CFD) modeling of historic buildings based on measured values. Although the heating was turned on in the meeting room in winter, heat loss caused by low thermal performance, airtightness, and inflow of cold air caused local thermal discomfort. Individuals seated near the windows had a temperature difference of up to 2.6 °C between the head and ankle levels. Heat loss was identified from the exterior walls and windows, with air infiltration significantly affecting indoor thermal comfort. The airtightness of the window frames of historic buildings was low, thus necessitating related improvement in heat and energy retrofit scenarios. This study propose a suitable approach to resolve this problem.